Dynamic capabilities: An exploration of how firms renew their resource base - Ambrosini, Veronique; Bowman, Cliff; Collier, Nardine (Blackwell Publishing Ltd, 2009)
The aim of this paper is to extend the concept of dynamic capabilities. Building on prior research, we suggest that there are three levels of dynamic capabilities which are related to managers‟ perceptions of environmental dynamism. At the first level we find incremental dynamic capabilities: those capabilities concerned with the continuous improvement of the firm‟s resource base. At the second level are renewing dynamic capabilities, those that refresh, adapt and augment the resource base. These two levels are usually conceived as one and represent what the literature refers to as dynamic capabilities. At the third level are regenerative dynamic capabilities, which impact, not on the firm‟s resource base, but on its current set of dynamic capabilities i.e. these change the way the firm changes its resource base. We explore the three levels using illustrative examples and conclude that regenerative dynamic capabilities may either come from inside the firm or enter the firm from outside, via changes in leadership or the intervention of external change a
Keywords: dynamic capabilities; environmental dynamism; managers; resource based view